Titanium tetrachloride as novel working fluid for high temperature Rankine Cycles: Thermodynamic analysis and experimental assessment of the thermal stability. (25th August 2016) - Invernizzi, C.M.; Iora, P.; Bonalumi, D.; Macchi, E.; Roberto, R.; Caldera, M.
Highlights: Titanium tetrachloride is proposed as new fluid in high temperature Rankine cycles. We show experimentally that it is remarkably stable at temperatures up to 500 °C. Resulting plant efficiencies of 35–40% are higher than state-of-the-art ORCs. Its high reactivity with water poses some concerns in the design of a power plant. Abstract: In this paper, Titanium tetrachloride (TiCl4 ) is analyzed/assessed and proposed as a new potential working fluid in Rankine Cycles. Besides its good thermodynamic properties, TiCl4 is in fact a fairly low cost, non-carcinogenic fluid, with zero Global Warming Potential (GWP) and Ozone Depleting Potential (ODP) and it is currently employed in high temperature industrial processes. It is however very reactive with humid air and water. A preliminary thermodynamic analysis confirms its possible application in power plants with maximum temperature up to 500 °C, considerably higher than the ORC state-of-the-art technology, performing electrical efficiencies as high as 35–40%. This suggests the potential use of TiCl4 as an alternative fluid in ORCs allowing the exploitation of high temperature sources (up to 500 °C), typically used in steam cycles. To assess the possibility of operating the cycle in such high temperature conditions, we carried out an experimental thermal stress analysis, showing that the fluid is remarkably stable at temperatures up to 500 °C, even in presence of P91 and Cupronickel, two materials typically employed in the high temperature section of power cycles.